Finger Licious Enterprise / Nurhairatul Hazwani Halimi ... [et al.] - Halimi, Nurhairatul Hazwani; Sulaiman, Mohammad Arif Danial; Mohamed Ramli, Muhammad Aiman Nurhakim; Azman, Muhammad Sharihin Fairusz (2021)
Finger licious enterprise is a new business in the city of Bukit Mertajam. The term Finger Licious was chosen because we believe it accurately depicts how our food service would satisfy our customers' hunger. Not only will it satisfy hunger, but it will also help to establish a stronger community. We also want to create a dish that fulfils all of their demands and that they can share with their family and friends. Our restaurant, Finger Licious Enterprise, is based on a mix culture of Korean and Malay food that will provide a unique sensation for most people's taste buds. This concept arose from the observation of Korean food enthusiasts who desired to have a unique experience while eating Korean food. Because our firm is listed as a freshly launched business in the market, it is evident that there are some elements that we must consider in order for our company to compete with competitors and meet client needs, as there are many people active in business nowadays. Our company is led by five key employees: the general manager, the administrative manager, the marketing manager, the operation manager, and the financial manager. All of us play an important part in running the firm and ensuring its success. According to our observations, we are targeting a wide range of clients because our company's location in the heart of the city will attract them. Our company's location is quite advantageous because it is close to shop lots and residential regions. With our business financial situation statement, we feel we will be able to reach our business aim. With the wonderfully outstanding quality that our company provides, we are confident that positive word about our goods will spread among customers. Finally, we hope that Finger Licious will become a well-known food business and will be able to supply more services from time to time. We also believe that as the human population grows, so will the need for our food services. Last but not least, it is our joy to serve as a model for others who want to start a foodstuff business.